2021
DOI: 10.1155/2021/5873007
|View full text |Cite|
|
Sign up to set email alerts
|

Huayu Tongluo Recipe Attenuates Renal Oxidative Stress and Inflammation through the Activation of AMPK/Nrf2 Signaling Pathway in Streptozotocin- (STZ-) Induced Diabetic Rats

Abstract: Diabetic nephropathy (DN), a severe microvascular complication of diabetes, is one of the leading causes of end-stage renal disease. Huayu Tongluo Recipe (HTR) has been widely used in the clinical treatment of DN in China, and its efficacy is reliable. This study aimed to explore the renoprotective effect of HTR and the underlying mechanism. Male Sprague-Dawley rats were fed with high sugar and fat diet combined with an intraperitoneal injection of STZ to establish the diabetic model. Rats in each group were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“… 28 , 29 Persistent hyperglycemia induced by STZ was confirmed as T2DM stage, 12 , 13 and abnormal renal function due to podocyte injury was considered the DN stage. 14 Serum TNF-α and IL-1β were tracked and compared in the above three stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 Persistent hyperglycemia induced by STZ was confirmed as T2DM stage, 12 , 13 and abnormal renal function due to podocyte injury was considered the DN stage. 14 Serum TNF-α and IL-1β were tracked and compared in the above three stages.…”
Section: Discussionmentioning
confidence: 99%
“…The 24 h urine volume (UV) was recorded, and the collected urine was stored in a −80°C freezer for later analysis. The 24h-UP and urine creatinine (UCr) levels were measured with commercial kits (Jiancheng Bioengineering Company, Nanjing, China), and the serum SCr and BUN levels 14 were determined with AU5800 ISE biochemistry analyzers (Beckman Coulter, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…There are various pathways like renal apoptosis, oxidative stress, nitrosative stress and inflammation to which the diabetic nephropathy pathogenesis has been tied (Hara et al, 2020; Li et al, 2021; Navarro‐González et al, 2011). Several evidences support an undeniable fact that excessive generation of reactive oxygen species, and hence, oxidative stress is triggered by hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidences support an undeniable fact that excessive generation of reactive oxygen species, and hence, oxidative stress is triggered by hyperglycaemia. A critical role is played by oxidative stress in the pathogenesis of diabetic nephropathy (Li et al, 2021). Reports have demonstrated that hyperglycaemia‐induced oxidative and nitrosative stress is responsible for causing inflammation, which activate glomerulus mesangial cells and accelerate renal impairment (Yoh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Spleen tyrosine kinase are the potential therapeutic target of flavanomarein to ameliorate high glucose-induced extracellular matrix (ECM) against DKD ( Zhang et al, 2020a ). Additionally, Yiqi Jiedu Huayu decoction and Huayu Tongluo recipe suppress diabetic kidney injury in STZ-induced rat model via modulating AMPK pathway ( Li et al, 2021 ; Xuan et al, 2021 ).…”
Section: Therapeutic Mechanism Of Chinese Herbal Medicine In Diabetic...mentioning
confidence: 99%